Cerebellar contribution to threat probability in a SCA6 mouse model. Issue 22 (16th June 2022) - Bohne, Pauline; Rybarski, Max; Mourabit, Damian Boden-El; Krause, Felix; Mark, Melanie D
Abstract: Fear and anxiety have proven to be essential during the evolutionary process. However, the mechanisms involved in recognizing and categorizing threat probability (i.e. low to high) to elicit the appropriate defensive behavior are yet to be determined. In this study, we investigated the cerebellar contribution in evoking appropriate defensive escape behavior using a purely cerebellar, neurodegenerative mouse model for spinocerebellar ataxia type 6 which is caused by an expanded CAG repeat in exon 47 of the P/Q type calcium channel α1A subunit. These mice overexpress the carboxy terminus (CT) of the P/Q type calcium channel containing an expanded 27 CAG repeat specifically in cerebellar Purkinje cells (CT-longQ27 PC ). We found that our CT-longQ27 PC mice exhibit anxiolytic behavior in the open field, elevated plus maze and light/dark place preference tests, which could be recovered with more threatening conditions such as brighter lighting, meowing sounds and an ultrasound repellent. Their innate fear to find safety in the Barnes maze and visual cliff tests was also diminished with subsequent trials, which could be partially recovered with an ultrasound repellent in the Barnes maze. However, under higher threat conditions such as in the light/dark place preference with ultrasound repellent and in the looming tests, CT-longQ27 PC mice responded with higher defensive escape behaviors as controls. Moreover, CT-longQ27 PC mice displayed increased levels of CT-labeled aggregates compared with controls. Together these data suggest that cerebellar degeneration by overexpression of CT-longQ27 PC is sufficient to impair defensive escape responses in those mice.